2011
DOI: 10.1080/02640414.2011.578149
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and patterns of physical activity practice among Spanish university students

Abstract: The purpose of the present study was to investigate the socio-demographic and lifestyle determinants of physical activity practice, as well as the motivations for being or not being physically active in Spanish university students. A representative sample of students from a Spanish university (n = 2,051; 42.1% males; mean age 21.9, s = 4.8 years) participated in the present cross-sectional study. A questionnaire including questions regarding lifestyle, dietary habits, parents' characteristics, and physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
8
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 29 publications
9
71
8
15
Order By: Relevance
“…Suboptimal calcium and magnesium dietary intake increases the risk of cardiovascular disease (CVD), insulin resistance, type 2 diabetes, hypertension and osteoporosis [31,34]. Additionally, high dietary phosphorus intake increases the risk of CVD in subjects with normal kidney function and causes hormonal disturbances related to bone health [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal calcium and magnesium dietary intake increases the risk of cardiovascular disease (CVD), insulin resistance, type 2 diabetes, hypertension and osteoporosis [31,34]. Additionally, high dietary phosphorus intake increases the risk of CVD in subjects with normal kidney function and causes hormonal disturbances related to bone health [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lake et al [25] demonstrated that active subjects aged 16-20 years consume less fat and more carbohydrates in comparison with their sedentary counterparts. Similarly, many studies have demonstrated a significant positive relationship between fruit and vegetable consumption and participation in physical activity in adolescents and young adults [1,30,34]. Moreover, Barzegari et al [3] noted better nutrition knowledge and food habits in active college students.…”
Section: Introductionmentioning
confidence: 99%
“…However, this panorama was also not particular to this population since other studies (e.g. Canada (22) , the United States (23) , Portugal (5) and Spain (24) ) also found similar profiles to those of students in higher education in relation to frequency and adherence to practicing sports, thereby showing that both (adhesion and frequency to practicing sports) do not reach the recommended minimum frequency in this population.…”
Section: Discussionmentioning
confidence: 60%
“…Romaguera et al [5] reported that physical activity was positively related to eating fruits and vegetables and negatively related to smoking tobacco. Also, Brandao et al [6] reported that female college students tend to be more inactive in the upper grade.…”
Section: Introductionmentioning
confidence: 99%